Regional Volume Table for White Cedar Dysoxyllum Malabaricum Bedd. (Data from Karnataka) - Rai, S. N. (Indian Forester, 1979)
Volume tables for White Cedar Dysoxyllum malabaricum Bedd. tree have been prepared by the method of linear regression. The model used is V=a+b D2H. The equation gives highly significant result. Table for the total wood (over bark) has been given.